Gen z garda terdepan perubahan, mengawal demokrasi di era digital - Sari, Fitri (Maliki Interdisciplinary Journal, 2025)
General elections are a crucial pillar of Indonesia’s democratic system, each implementation always presenting its own dynamics and challenges. Generation Z, those born between 1997 and 2012, plays a significant role in addressing these changes. In this context, Generation Z plays an active role in disseminating information, understanding political visions and missions, and engaging in public conversations through social media. They demonstrate a high level of political awareness, participate in the electoral process, and utilize digital technology to innovate in political campaigns. Their involvement influences not only the direction of election results but also the formation of policies and the social issues that arise in society. With the constructive role of Generation Z, Indonesian democracy is expected to become more advanced and adaptable to changing times.